377 Effects of fiber blend and prebiotic supplementation on food intake, apparent total tract digestibility, fecal quality of adult dogs. (7th December 2018) - Nogueira, J; He, F; Oba, P; Mangian, H; de Godoy, M
Abstract: Prebiotics and dietary fibers are non-digestible ingredients that may confer benefits to the host by selectively stimulating beneficial intestinal bacteria. This experiment tested the effects of a blend of prebiotics and fibers on gastrointestinal health of adult dogs. Four diets containing either 5% of cellulose, 5% of fiber blend, 0.02% of prebiotic or 5% fiber blend plus 0.02% of prebiotic were formulated to meet or exceed the AAFCO (2017) nutritional requirements for adult dogs. Eight adult female beagles (mean age 4.2 ± 1.1 yr; mean BW = 10.8 ± 1.4 kg; mean BCS = 5.8 ± 0.6) were randomly assigned to one of the 4 dietary treatments using a replicated 4x4 Latin square design. Each experiment period consisted of 14 days (10 days of diet adaption + 4 days of total and fresh fecal and total urine collection). Food intake, fecal and urine output were measured and sampled for macronutrient analysis and digestibility calculations. Blood samples were collected at the end of each period for serum chemistry analysis and complete blood count. The data were analyzed using MIXED procedure, SAS, version 9.4. All animals remained healthy throughout the study with serum metabolites being within reference ranges for adult dogs. All diets were well accepted by the dogs, resulting in similar daily food intake among treatments. Likewise, fecal output and scores did not differ (P > 0.05) among dietary treatments, with the latter being within ideal range (2.5–2.9). All diets were highly digested by dogs, and had similar (P > 0.05) apparent total tract digestibility of dry matter (81.6–84.4%), organic matter (86.4–87.3%) and crude protein (86.6–87.3%). Thus, the data gathered herein suggest that these prebiotic and fiber blends are well tolerated by dogs and do not cause detrimental effects on fecal quality or nutrient digestibility.